Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Nasabah - M Yusuf Asrofi; Ajeng Aquinia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In this day and age, company competition is getting tougher, so companies must innovate to build consumer comfort for the services provided by the company.The purpose of this study is to analyze the effect of Service Quality and Corporate Image on Customer Satisfaction. Implementation of research on customers who use the services of the Setia Kawan Cepiring cooperative. The method used in this study is a quantitative research method. The sampling technique in this study was used as a sampling technique and a total of 100 respondents were obtained from 4235 total customers in 2022. Data analyzed through validity test with KMO and Component Matrix, reliability test with Cronbach alpha, and multiple regression analysis. The results showed that service quality variable has a significant positive effect on customer satisfaction and corporate image has a significant positive research effect on customer satisfaction. The better of service quality and corporate image will be following by, the higher customer satisfaction in the next period.